AB0606 Mortality associated factors to idiopathic inflammatory myopathies (IIMS). (15th June 2017) - Costi, AC; Sansinanea, P; Pena, C; Testi, A; Salas, A; Marcos, J; Arturi, V; Vulcano, A; Pera, M; Salinas, R García; Maldonado, R Aguila; Var, L García; et al.
Abstract : Background: Idiopathic inflammatory myopathies (IIMs) include a group of muscular diseases characterized by the presence of muscle inflammation. The mortality of the IIMs has been estimated between 13 and 50%. Objectives: To evaluate mortality rate and associated factors in patients with IIMs. Methods: Retrospective, observational study, where patients with IIMs (Bohan & Peter 1975) were included. Data were obtained from medical records from patients with myopathy (Increase CK, muscle weakness, cutaneous involvement, interstitial lung involvement) evaluated in a reference rheumatology center of Argentina (1992–2016). Descriptive statistics were performed. Chi2 test, Student's test or Mann Whitney as appropriate multivariate logistic regression analysis. Results: From 102 patients evaluated 89 enter the study, 73% were female. Mean age at diagnosis 48±14 years. Clinical Manifestations: Skin involvement 77% (erythema Heliotrope 51%, rash on the neck and V-sign 60%, back and shoulders 50%, photosensitivity 60%, Gottron's papules 50%, pruritus 33%, erythema peri nail 21%), pulmonary involvement 19% Raynaud 28%, muscle weakness 86%, muscle weakness of the neck 33%, respiratory muscles 13%, myalgias 60% and dysphagia 53%. Muscle biopsy: performed in 36/89 with pathological findings in 83%, electromyogram performed in 35%. Intensive care unit admission 14/89 (16%). Laboratory: raised CPK 68% with an mean value 3527 IU/ml, raised Transaminase 60%, ANA positive 65%, SSA/RO 25%, Jo1 4.4%, RNP 7%, increased CRP 28% and ERA 59%. Clinical Subtypes IIMs: Dermatomyositis (DM): 61%, Antisynthetic syndrome (AS): 6%, Myopathy associated with connective tissue disease: 19%, Associated with statins: 4, 4%, Polimyositis: 10%. Association with neoplasia was observed in 15%. Treatments: Corticoids pulses 21%, corticoids 97% (mean starting dose 45 mg meprednisone), methotrexate 77%, hydroxychloroquine 36%, azathioprine 30%, cyclophosphamide 16%, intravenous immunoglobulin 15%, biological 10% and cyclosporine 3%. Mortality was 22.5% (20/89 patients), CI95 (14.3–32.5). Mean time from diagnosis to the event was 18 months. The primary cause of death was sepsis 14/20 (70%). Conclusions: Mortality of patients with inflammatory myopathies was 22%, and the primary cause was infectious. In the analysis of multiple variables, male sex, presence of neoplasms and serious infectious complications were significantly factors associated with mortality. References: J Clin Rheumatol 2016; 22: 51–56. Med Clin 1999; 112:521–6. Disclosure of Interest: None declared